Electronic Banking and Bank Performance: Evidence from Nigeria - Adegboyega Raymond; Ariyibi Mayowa Ebenezer; Olaiya Isiag Kehinde; Yunusa Adewale Lateef (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2022)
The innovative advancement of the financial system has made deposit money banks all over the globe adopt a technological mode of meeting the customer’s needs, so it has to improve the level of deposits and withdrawals. Hence due to this innovation, this study examines the impact of electronic banking on bank performance in Nigeria. The secondary data collected from the central bank of Nigeria Statistical bulletin from 2009-2017 were subjected to Johansen Co-integration and Vector Error Correction Method (VECM). The findings revealed through the Johansen Co-integration results depict a long-run relationship between the variables. The Fully Modified Least Square depicts that Mobilepay and Webpay have a significant negative effect on NIM (Net Interest margin) while POS (Point of Sale) has a significant positive effect on NIM (Net Interest Margin). The bank should make sure POS (Point of Sale) and Website/Internet transactions are made available to rural and urban areas, so has to encourage different classes of account holders to transfer and receive cash quickly.How to Cite:Raymond, A., Ebenezer, A. M., Kehinde, O. I., & Lateef, Y. A., (2022). Electronic Banking and Bank Performance: Evidence form Nigeria. Signifikan: Jurnal Ilmu Ekonomi, 11(2), 371-382. https://doi.org/10.15408/sjie.v11i2.15540.JEL Classification: G21, G32, G51